Vertical Distribution in Inverted Nonfullerene Polymer Solar Cells by Layer‐by‐Layer Solution Fabrication Process. Issue 11 (18th September 2021) - Xie, Xiangdong; Liao, Jianping; Liu, Junqin; Meng, Yilong; Huang, Wenyin; Zhan, Xiaozhi; Wang, Li-Ming; Li, Qingduan; Zhu, Tao; Liu, Shengjian; Cai, Yue-Peng
Abstract : The layer‐by‐layer (LBL) solution process is a potential technology for future application of polymer solar cells (PSCs), while the vertical composition distribution evolution of the LBL active layer is still unknown. In this work, taking advantage of the LBL method and inverted device structure, inverted LBL‐processed PSCs are fabricated with polymer donor PM6 and nonfullerene small‐molecule acceptor Y6. As‐prepared devices with PM6 as the bottom layer and Y6 as the top layer exhibit low power conversion efficiencies (PCEs), while the post‐treatment brings a significant boost on the device performance (from 8.5% to 14.4%). The vertical composition distribution evolution of LBL photoactive layer is investigated by the combination of surface atom distribution analysis via X‐ray photoemission spectroscopy (XPS) and composition distribution across the bulk of the films via neutron reflectivity (NR). The findings can potentially offer positive guidance for the further utilization of organic photovoltaics. Abstract : Neutron reflectometry (NR) is used to probe the vertical composition distribution patterns of layer‐by‐layer (LBL) films in an inverted organic solar cell with structure of ITO/ZnO/LBL layer/MoO3 /Ag. Devices with post‐annealing demonstrate improved donor:acceptor paths and obtain a high power conversion efficiency (PCE) of 14.4%. Importantly, the inverted LBL devices exhibit excellent thermal stability.